TREE SPECIES COMPOSITION OF 1.8 HA PLOT SAMBOJA RESEARCH FOREST: 28 YEARS AFTER INITIAL FIRE - Subekti Rahayu; Sambas Basuni; Agus Priyono Kartono; Agus Hikmat; Meine van Noordwijk (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2017)
Repeated forest fires highly impact on tree species composition. Forest planning requires information about the current condition of species composition. This paper investigates the current tree composition of natural regeneration after repeated forest fires, regeneration process after repeated fires, and strategy of secondary growth related to ecological restoration issues. Re-observation of the 1.8 hectares permanent plot in Samboja Research Forest was conducted in 2011. All trees with diameters above 10 cm at breast height (DBH) were re-numbered and mapped. Herbarium specimen was collected for species identification. Number of taxon was determined, Important Value Index was calculated, species trait of light response was identified based on the references and dispersion index species was calculated. Results show after twenty eight years initial forest fire, 191 species naturally regenerated in the burnt area. Macaranga gigantea, a light demanding pioneer species of Euphorbiaceae was the most dominant species, followed by Vernonia arborea belonging to Asteraceae. Both, M. gigantea and V. arborea had clumped distribution. Eight species identified survived from repeated fires, are Anthocephalus chinensis, Dipterocarpus cornutus, Diospyros borneensis, Eusideroxylon zwageri, Shorea ovalis, Syzygium borneensis, Pholidocarpus majadum and Vatica umbonata. All surviving species was distributed uniformly in the plot. Dominant pioneer species which has grown after repeated fires indicates that the current condition of burnt forest is in the early succession. Protecting forest, assisting natural regeneration and monitoring dominant species are suggested as activities for the ecological restoration.